Assessment of Knowledge, Attitude, and Practice towards Prevention and Control of Malaria in Halaba Town, Southern Ethiopia, 2017 - Tadesse Menjetta (Journal of Tropical Medicine)
Background. Malaria is one of the primary public health problems in Ethiopia. Therefore, assessment of situation of the disease and communities’ knowledge and perceptions about this disease is necessary to introduce appropriate preventive and control measures. Hence, this study was aimed to assess the knowledge, attitude, and practice towards malaria in Halaba town, SNNPR, Ethiopia. Methods. A community-based cross-sectional study was conducted in Halaba town from June 2017 to September 2017. A multistage random sampling technique was used to select the study participants. A total of 421 were interviewed to assess their knowledge, attitude, and practice towards malaria. Results. About 280 (66.5%) respondents had ever heard of malaria. Most of the respondents (63.4%) attributed the cause of malaria to mosquito bites. However, some of the respondents (36.6%) mentioned contact with malaria patients, lack of personal hygiene, staying together, and transmission via breathing as the causes of malaria. Sleeping under mosquito nets, draining stagnant water, and indoor residual spraying were the most frequently mentioned malaria preventive measures perceived and practiced by the respondents. Conclusions. A high level of knowledge about the cause, transmission, and preventive methods of malaria was detected among the community in Halaba town. However, a significant proportion had misconceptions about the cause and transmission of malaria suggesting the necessity of health education to raise the community’s awareness about the disease.